Analysis of installation of ducted propeller (kort nozzle) on cargo ship after maintenance - Oktovianus Bura, Romie; Nengah Putra Apriyanto, I; Dwi Susanto, Arica (International Journal of Engineering and Technology, 2019)
The country of Indonesia is a country of export and import of international trade goods. A cargo ship is a type of ship that carries cargo from one port to another. To meet the needs of international trade must carry out various patterns of ship maintenance by carrying out maintenance. The problem is that conventional propellers are currently installed, at high rotations there can be cavitation of air bubbles around the propeller which decreases propeller efficiency. To improve the conditions above, a Ducted Propeller was installed. From the matching calculations that have been done, the propeller that suits the needs of the ship is a Ka 3.65 type using a ducted propeller. By using a Ka 3.65 type propeller. The power needed is 2239.99 kW the efficiency that can be achieved is 55%, sfoc 214 g / kW, and the speed of the ship will be 16.09 knots at 100% rotation of the propeller, and at 85% the power needed 1375.84 kW, sfoc 214 g / kW, speed reaches 9.88 knots. The difference in speed between conventional blades with type B 4.55 with type Ka 3.65 that uses a cort nozzle is 16.09 knots-13.05 knots = 3.04 knots. Or you can experience a speed increase of (3.04 / 13.05) x100 = 23.29.
Keywords: Ship Resistance; Power Boats; Propeller; Ship Propulsion; Engine Propeller Matching; Cargo Ship.